The effects of a reduced-exertion high-intensity interval training protocol on measures of cardiovascular and metabolic health in physically inactive individuals - Makela, Michael (My University, 2020)
Cardiometabolic diseases such as diabetes and cardiovascular disease are a growing threat to the quality of life of the population. Exercise is a frontline approach to treat and prevent cardiometabolic disease and its associated risk factors. The majority of individuals, however, are physically inactive and fail to meet weekly physical activity guidelines primarily due to time-constraints. High-intensity interval training (HIIT) is a time-efficient method of exercise for improving physical fitness and reducing cardiometabolic risk factors compared to moderate-intensity continuous training (MICT). Recent research indicates that the number of repetitions and duration of high-intensity intervals can be reduced without attenuation of health benefits. This study recruited nine physically inactive but otherwise healthy participants (6 female, 3 male) which engaged in a 6 week reduced-exertion HIIT protocol. Participants were assessed before and after a 2 week run-in period, and again upon completion of the exercise protocol to assess the effect on predicted aerobic capacity (VO2max), resting heart rate (HR), resting blood pressure, heart rate variability (HRV), fasting blood glucose, peak power, mean power, body mass, and body fat %. Participants improved predicted VO2max F(2,16)=6.33, p=.009, peak power F(2,16)=10.84, p=.001, and mean power F(2,16)=20.87, p=.00006, but no changes were observed in body mass, body fat %, resting HR, resting blood pressure, resting HRV, and fasting blood glucose. In conclusion, a reduced-exertion HIIT protocol with minimal time-commitment improved predicted VO2max, peak power, and mean power and is a time-efficient alternative or adjunct method of exercise for eliciting health benefits in physically inactive individuals.
Keywords: High-intensity interval training (HIIT); Cardiovascular and metabolic health; Cardiometabolic benefits of exercise